Knockdown of Adra2a Increases Secretion of Growth Factors and Wound Healing Ability in Diabetic Adipose-Derived Stem Cells - Xiangyuan Zhao; Yong Zhang; Xinzhen Zuo; Shubai Wang; Xiao Dong (Stem Cells International)
Studies showed that compared to normal adipose-derived stem cells (ASCs), ASCs from type 2 diabetic (T2D) mice were less effective in treating diabetic cutaneous wounds. However, the mechanisms remain unclear. Our transcriptomic profiling comparison showed that the expression of α2A-adrenergic receptor (Adra2a) was significantly increased in ASCs from T2D mice (T2D ASCs). Therefore, the purpose of this study was to investigate whether the elevated Adra2a is involved in the diminished wound-healing capabilities of T2D ASCs. RNA-seq was used to compare the transcriptomic profiles of T2D and normal ASCs. The differential genes were verified by real-time RT-qPCR. Clonidine was used to active Adra2a, and lentivirus-mediated RNAi was used to knockdown Adra2a. The secretion and expression of growth factors were detected by enzyme-linked immunosorbent assay (ELISA) and real-time RT-qPCR, respectively. The cAMP and PKA activity were also detected. Wound healing abilities of various ASCs were assessed in T2D mouse excisional wound models. The results showed Adra2a agonist clonidine decreased the expression and secretion of growth factors, cAMP content, and activity of PKA in ASCs, while Adra2a knockdown T2D ASCs showed the opposite effects. Adra2a knockdown T2D ASCs also showed increased wound-healing capabilities compared to untreated T2D ASCs. Altogether, T2D increased Adra2a expression, which may subsequently decrease the expression and secretion of growth factors and eventually diminish the wound-healing capabilities of T2D ASCs. Adra2a knockdown can restore the secretion of growth factors in T2D ASCs and then accelerate the wound healing, which may provide a new possibility in the treatment of diabetic wounds.